Modeling of High Pressure Loss (Head Loss) in a Flow Measurement Unit with Various Pipe Network Manifold Openings - Irianto, Djoni (Engineering And Technology Journal, 2024)
The head loss in water flowing through pipes often turns out to be different from what we assume, which is the occurrence of incompressible flow. However, this assumption is not always true because the flow pattern inside the pipe is not visible and can only be measured with precise equipment. The presence of water in the pipes can only be tested on a clear scale, especially when it is part of the network within a multi-story building. Determining the need for a pipe network within a building is not an easy calculation due to differences in length, diameter, and bends. Hydraulic experts often overlook these differences, which can become a problem when clogs occur during the flow process. To find a solution to this problem, it is necessary to conduct tests using a device called a Water Measurement Unit. This is rarely done in laboratories. Testing the water pressure with this device requires various instruments and a variety of valve openings supplied with pressurized water by a pump at a certain capacity. To analyze the flow rates resulting from the tests with different valve openings, researchers test and measure the flow rate capacity for each opening, starting with openings of 0.5, 0.75, 1.00, and so on. They read the instrument, move the copper from one height to another, and create a graph of the test results in the form of a pair of connectors. The researchers test the device and its openings three times for each opening, recording and mapping the pressure values and the time it takes on the measuring instrument. Subsequently, the results of the pressure test (Head Loss) are recommended to provide information to water pipe installation planners that the test results with various valve openings under certain conditions have different pressure values and travel times. It turns out that in the placement of hose or copper number 2, stability is observed with pressure, and there is no significant differential pressure increase. In the experiment with hose or copper number 2, it can be said that everything is stable enough to conclude that there is no head loss, and it is recommended to be safe for modeling.